Novel topic detection method for microblog based on SVM filtration - Jun-xia CHENG; Zhi-tang LI; Ming-guang ZOU; Jin XIAO (Tongxin xuebao)
A detection method based on SVM filtration was proposed.The method uses text feature as imported vectors to filtrate microblog news,reducing the amount of calculation greatly.A single-pass clustering algorithm based on the improvement of high-frequency words sorting was proposed,which can detect isolated points commendably.Experimental results show that the method can detect news topics from massive microblog data efficiently.